2015
DOI: 10.20884/1.anprod.2015.17.1.484
|View full text |Cite
|
Sign up to set email alerts
|

Phytobiotic Properties of Garlic, Red Ginger, Turmeric and Kencur in Growing Ducks

Abstract: Abstract. Phytobiotic properties of garlic (Allium sativum), turmeric (Curcuma domestica), red ginger (Zingiber officinale) and kencur (Kaempferia galangal) were studied using standard in vitro antibacterial test and in vivo feeding trial with ducklings. In the in vitro experiment, potency of aqueous extract of these phytobiotic agents were tested against Salmonella pullorum and Escherichia coli. Feeding trial was carried out for 6 week starting at day 28 using ducklings fed diets supplemented with 1% of each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Meanwhile, 5 g of turmeric per kg of feed does not affect the BW and feed conversion of broiler chickens although has an impact on the feed consumption and conversion from the starter period to the finisher period [26]. On the other hand, there are studies that show a negative impact of turmeric at the level of 1% on feed intake, weight gain, and feed conversion [27]. Moreover, Attia [22] reported that the addition of turmeric combined with other herbs at a balanced level (0.15:0.15) has a significant influence on the feed conversion parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, 5 g of turmeric per kg of feed does not affect the BW and feed conversion of broiler chickens although has an impact on the feed consumption and conversion from the starter period to the finisher period [26]. On the other hand, there are studies that show a negative impact of turmeric at the level of 1% on feed intake, weight gain, and feed conversion [27]. Moreover, Attia [22] reported that the addition of turmeric combined with other herbs at a balanced level (0.15:0.15) has a significant influence on the feed conversion parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Adding feed additives to the diets of laying poultry has been shown to improve feed efficiency, animal health, and productivity (Ismoyowati & Sumarmono, 2019). For example, the inclusion of several Phyto biotics improved the performances of growing ducks (Ismoyowati et al, 2015). Herbal additives (phytogenic and medicinal compounds derived from plants) could act as a substitute for the growth-promoting antibiotic (Masoud-Moghaddam et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Even though spice plants (empon-empon) need to be developed because not only as ingredients for spices or in cooking but family medicinal plants can be used as an alternative to maintain and care for our health naturally without any side effects such as ginger, turmeric, kencur, and so on. -other (Ismoyowati et al, 2015).…”
Section: General Descriptionmentioning
confidence: 99%